1978
DOI: 10.1007/bf00644609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various cephalosporins on the proximal tubule of the human kidney

Abstract: Cephamandol 6.0 g, cephazolin 6.0 g or cephacetrile or cephalothin 8.0 g were administered as short-term infusions on 3 consecutive days to informed volunteers, who had no history or evidence of impairment of renal function. There were 15 subjects in the cephamandol, cephacetrile and cephalothin groups and 14 subjects in the cephazolin group. Alanine-aminopeptidase, a characteristic tubule enzyme, was determined in a 24-hour urine 2 days before administration, during the 3 day administration and on the 4 subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Similar findings were obtained, assessing acute renal toxicity of ciclosporin, aminoglycosides and radiocon trast media [30, 44,52,[66][67][68][69][70]. However, patients' sus ceptibility to drug-induced toxic renal injury varied greatly [13,67], The excretion of tubular membrane pro teins in the urine after administration of low-osmolar nonionic X-ray contrast media (iopamidol 832 mosm/ kg) was significantly lower than after injection of highosmolar diatrizoate (2,100 mosm/kg) [69], This suggests that, aside from preexisting diseases and renal altera tions, the tubulotoxic effect of radiopaque contrast me dia depends mainly on their osmolality [65,70].…”
Section: Tubular Proteins In the Urine Of Patients Under Defined Clinsupporting
confidence: 69%
“…Similar findings were obtained, assessing acute renal toxicity of ciclosporin, aminoglycosides and radiocon trast media [30, 44,52,[66][67][68][69][70]. However, patients' sus ceptibility to drug-induced toxic renal injury varied greatly [13,67], The excretion of tubular membrane pro teins in the urine after administration of low-osmolar nonionic X-ray contrast media (iopamidol 832 mosm/ kg) was significantly lower than after injection of highosmolar diatrizoate (2,100 mosm/kg) [69], This suggests that, aside from preexisting diseases and renal altera tions, the tubulotoxic effect of radiopaque contrast me dia depends mainly on their osmolality [65,70].…”
Section: Tubular Proteins In the Urine Of Patients Under Defined Clinsupporting
confidence: 69%
“…Nevertheless, approximately 40% of cefuroxime is eliminated by tubular secretion (7) (cefotaxime quantitative data are not yet available). In contrast to cefamandole, cefoxitin, and cefuroxime, cefotaxime undergoes a deacetylation in vivo similar to that of cephalothin (13), which accounts for the major differences in the excreted urinary fraction of cefotaxime (Table 3 (19,21). This is apparently due to increased shedding of the brush border membranes of the proximal tubules of the kidney.…”
Section: Resultsmentioning
confidence: 99%
“…At intervals of 1 week 0.5-, 1-, and 2-g doses of cefotaxime were administered to each volunteer over 15 min, followed by sustaining infusions of 0.5, 1, and 2 g/h, respectively, for 3 consecutive hours ( In addition to these parameters, a specific attempt was made to evaluate the effect of cefotaxime on the proximal tubules of the kidney. AAP is an enzyme located primarily on the brush border membranes of the renal tubules, and several authors have demonstrated that damage to the proximal tubules (either drug induced or due to an inflammatory process) is reproducibly associated with an increased urinary AAP output (4,(18)(19)(20)(21)25). AAP activity was determined by a spectrophotometric method using alaninep-nitranilide (Roche Reagents; catalog no.…”
Section: Materiais and Merhodsmentioning
confidence: 99%